TEACHERS’ PERCEPTION ON MOTIVATIONAL STRATEGIES IN EFL TEACHING A SURVEY STUDY AT JUNIOR HIGH SCHOOLS IN KEBAYORAN LAMA - Maharini , May Triranto; Sari, Anita (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2021)
Teachers nowadays are not only expected to transfer the subject that the students need to know, but also they are expected to keep the students’ interest in learning English to reach the objective of the subject. Therefore, teachers’ awareness to make the students keep motivated is important. Proving his concern on this matter, Dörnyei, after doing his researches, formed some motivational strategies to be applied by EFL teachers in the classroom. Based on these strategies by Dörnyei, this study aims at finding out teachers’ awareness from eight junior high schools in Kebayoran Lama of the importance and the employment of the strategies in EFL classroom. This study is conducted using survey analysis. It successfully proves that most teachers in these eight junior high schools recognize the importance for the strategies to be implemented in their EFL classes. It also successfully finds that these teachers also recognize what strategies that get their concern the most in which showed the different result between the teachers of public junior high schools and private junior high schools. The last successful finding is proved by the statistical analysis that these strategies actually give influence on the students’ achievement. It is expected that this study can give insight into EFL teachers that motivational strategies are important to be implemented to motivate their students and these motivational strategies can help student achieve the objective of the subject, English as a Foreign Language.